Association of diabetes related self-care activities with glycemic control of patients with type 2 diabetes in Pakistan - Bukhsh, Allah; Khan, Tahir Mehmood; Sarfraz Nawaz, Muhammad; Sajjad, Hafiz; Chan, Kok Gan; Lee, Learn-Han; Goh, Bey-Hing (Dove Medical Press, 2018)
Objective: Association of various self-care activities on glycemic control of people with diabetes (PWD) in Pakistan is yet to be explored. The current study aimed to evaluate the association of various diabetes-related self-care activities with glycated hemoglobin (HbA1c) levels and to examine the predictive relationship of patients’ demographic variables with their self-care activities. Patients and methods: A cross-sectional study was conducted on adult PWD (N=218) who were diagnosed with type 2 diabetes mellitus of at least 1 year duration. Self-care activities were examined by using the Urdu version of Diabetes Self-management Questionnaire. Linear regression analysis was conducted to examine the significant predictors for diabetes-related self-care activities and glycemic control. Results: Mean age of the patients was 50.77±13.3 years. Poor glycemic control (HbA1c ≥7%) was observed in majority of the patients (83%). Linear regression analysis revealed that glucose management (β=-0.44; 95% CI-0.438,-0.209; P<0.001) was the strongest predictor for low levels of patients’ HbA1c, followed by dietary control (β=-0.19; 95% CI-0.248,-0.018; P=0.024) and physical activity (β=-0.17; 95% CI-0.165,-0.023; P=0.010), respectively. Linear regression analysis showed that use of oral hypoglycemic agents only (β=-0.218; 95% CI-0.956,-0.200; P=0.003) and higher education level (β=0.204; 95% CI 0.138, 0.777; P=0.005) were significant predictors for higher scores of patients’ self-care activities. Conclusion: The findings support that PWD having better self-reported self-care activities achieve better glycemic control. Patients’ self-care activities should be monitored on a regular basis, especially for those who are at risk of poor glycemic control.